2012
DOI: 10.1103/physrevd.86.054018
|View full text |Cite
|
Sign up to set email alerts
|

Self-consistency requirements of the renormalization group for setting the renormalization scale

Abstract: In conventional treatments, predictions from fixed-order perturbative QCD calculations cannot be fixed with certainty due to ambiguities in the choice of the renormalization scale as well as the renormalization scheme. In this paper we present a general discussion of the constraints of the renormalization group (RG) invariance on the choice of the renormalization scale. We adopt the RG based equations, which incorporate the scheme parameters, for a general exposition of RG invariance, since they simultaneously… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
60
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

8
1

Authors

Journals

citations
Cited by 86 publications
(65 citation statements)
references
References 76 publications
5
60
0
Order By: Relevance
“…When one applies the PMC, all nonconformal terms are systematically eliminated at each finite order. The PMC satisfies the self-consistency conditions of the renormalization group, such as reflectivity, symmetry, and transitivity [15]. The PMC scales are achieved by applying the RGE recursively.…”
Section: Introductionmentioning
confidence: 99%
“…When one applies the PMC, all nonconformal terms are systematically eliminated at each finite order. The PMC satisfies the self-consistency conditions of the renormalization group, such as reflectivity, symmetry, and transitivity [15]. The PMC scales are achieved by applying the RGE recursively.…”
Section: Introductionmentioning
confidence: 99%
“…Residual scale dependence and an estimation of unknown high-order contributions after applying the PMC scale-setting µ r (GeV) PMC scales (GeV) Eqs. (15,16,17,18) There are residual scale dependence due to unknown high-order terms, which however suffer from both the α ssuppression and the exponential suppression. Thus those residual scale dependence are generally small.…”
Section: Conv Pmcmentioning
confidence: 99%
“…The principle of maximum conformality (PMC) [11][12][13][14] has been suggested for the purpose of eliminating the conventional renormalization scheme-and-scale ambiguities. It has been found that the PMC satisfies all the self-consistency conditions of the renormalization group equation (RGE) or the β-function [15] and the renormalization group invariance, which has been applied for various processes, c.f. the reviews [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Also, it should be noted that the behavior of the renormalization and factorization scales is widely studied in Refs. [16][17][18][19][20][21]. The infrared renormalon effects in various inclusive and exclusive processes present one of the most important and interesting problems in perturbative QCD [22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%